Lithium takes to the road [all electric sports car].
This work presents an all-electric sports car, called the Fetish, unveiled in September 2004 by Venturi Automobiles of Monaco at the Paris Auto Show. Fetish relies on a lithium ion battery pack made from the type of cells normally found in portable electronics. Because of their high power density and despite concerns about flammability, lithium ion batteries are being eyed by makers of hybrid electric vehicles as an alternative to nickel metal hydride.
Keywords: Fetish; All-electric sports car; High power density; Hybrid electric vehicle; Lithium ion battery pack